Multidelay multiparametric arterial spin labeling perfusion MRI and mild cognitive impairment in early stage Parkinson's disease. Issue 4 (7th December 2018) - Suo, Xueling; Lei, Du; Cheng, Lan; Li, Nannan; Zuo, Panli; Wang, Danny J. J.; Huang, Xiaoqi; Lui, Su; Kemp, Graham J.; Peng, Rong; Gong, Qiyong
Abstract: Mild cognitive impairment (MCI), a well‐defined nonmotor manifestation of Parkinson's disease (PD), greatly impairs functioning and quality of life. However, the contribution of cerebral perfusion, quantified by arterial spin labeling (ASL), to MCI in PD remains poorly understood. The selection of an optimal delay time is difficult for single‐delay ASL, a problem which is avoided by multidelay ASL. This study uses a multidelay multiparametric ASL to investigate cerebral perfusion including cerebral blood flow (CBF) and arterial transit time (ATT) in early stage PD patients exhibiting MCI using a voxel‐based brain analysis. Magnetic resonance imaging data were acquired on a 3.0 T system at rest in 39 early stage PD patients either with MCI (PD‐MCI, N = 22) or with normal cognition (PD‐N, N = 17), and 36 age‐ and gender‐matched healthy controls (HCs). CBF and ATT were compared among the three groups with SPM using analysis of variance followed by post hoc analyses to define regional differences and examine their relationship to clinical data. PD‐MCI showed prolonged ATT in right thalamus compared to both PD‐N and HC, and in right supramarginal gyrus compared to HC. PD‐N showed shorter ATT in left superior frontal cortex compared to HC. Prolonged ATT in right thalamus was negatively correlated with the category fluency test ( p = .027, r = −0.495) in the PD‐MCI group. This study shows that ATT may be a more sensitive marker than CBF for the MCI, and highlights the potential role of thalamus and inferior parietal region for MCI in early stage PD.